The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages kind of social services we have outlined is so obvious that it may be worth while to point out that in any housing plan careful consideration should be given to providing space and buildings for the development of social services. For instance, estates in undeveloped areas should include accommodation for maternity and child welfare centres, nurseries, playgrounds, restaurants etc., and special provision should be made on some estates for the aged, crippled, tubercular and blind. There should be adequate shopping facilities on new Estates, and community centres should be established as an essential part of community life. The management of house property should be recognised as a job needing not only business ability and technical knowledge, but an understanding of human problems, and training in dealing with them, in other words social work training. While it is clearly impossible to provide trained housing managers for all the estates which need to be built during the next few years, steps should be taken to train more people as specialists in this form of social work, and also to provide such people as superintendents with a short training in social science, to include at least a knowledge of the structure of local government, an acquaintance with the social agencies and health services of his district. The selection of personnel for this work should be made with an eye to their 29 15X/2/464/1